Impact of the Dapivirine Vaginal Ring on Sexual Experiences and Intimate Partnerships of Women in an HIV Prevention Clinical Trial: Managing Ring Detection and Hot Sex - Laborde, Nicole D.; Pleasants, Elizabeth; Reddy, Krishnaveni; Atujuna, Millicent; Nakyanzi, Teopista; Chitukuta, Miria; Naidoo, Sarita; Palanee-Phillips, Thesla; Baeten, Jared M.; Montgomery, Elizabeth T. (AIDS and Behavior, 2018)
Vaginally-inserted HIV prevention methods have been reported to impact the sexual experience for women and their partners, and hence impacts acceptability of and adherence to the method. We analyzed in-depth interviews and focus group discussions about participants’ sexual experiences while wearing the ring, collected during the MTN-020/ASPIRE phase 3 safety and effectiveness trial of a dapivirine vaginal ring for HIV prevention in Malawi, South Africa, Uganda, and Zimbabwe. Most women reported that partners did not feel the ring during sex, however, women felt they had to manage their partners’ interaction with or reaction to the ring. In maintaining positive relationships, women were concerned about partners’ discovering ring use and about ensuring that partners had a good sexual experience with them. Finally women were concerned about how they themselves experienced sex with the ring. Some found that the ring made the vaginal environment more desirable for their partners and themselves
Keywords: Gender; HIV; Clinical trial; Vaginal ring; Sexual relationship; Sub-Saharan Africa